HISTOLOGICAL EFFECTS OF EUGENIA JAMBOLANA SEED EXTRACT ON LIVER OF ADULT ALBINO RATS - Rasheed, Sadaf; Tahir, Mohammad; Sami, Waqas; Munir, Bushra (Journal of Ayub Medical College Abbottabad, 2009)
Background: The therapeutic value of Eugenia jambolana, commonly known as ’˜Jamun’ in Hindi, has been recognized in different system of traditional medicine for the treatment of various conditions. Its seeds are used for the treatment of diabetes mellitus and hyperlipedemia by reducing the lipid levels in the body; this action is presumed to be due to blocking the action of enzyme 3-hydroxyl methyl glutaryl (HMG-CoA reductase in the liver. Herbal drugs are getting into use with the notion that these are relatively harmless; the practice has shown that many of them also have toxic effects. Since hardly any work is available on the toxic aspect of Eugenia Jamblana, the present study was planed to see the effect of ethanolic extract of Eugenia Jamblana on liver using albino rats as an experimental model. Methods: The animals were divided into three groups A, B and C. Group A served as a control and received only distilled water comparable to the experimental animals calculated according to their body weight, where as B and C served as experimental groups. 100 and 200 mg of ethanolic extract of Eugenia Jamblana was dissolved in one ml of distilled water each and was given orally for 30 days/kg body weight. Results: liver enzyme ALT and gamma GT were significantly raised when compared to the control group, p-value being <0.05. Histological studies showed ballooning degeneration of hepatocytes, focal areas of hepatocytes necrosis with lymphocytic infiltration, providing supportive evidence for biochemical findings indicative of functional derangement. The effect of the extract was not dose dependent. Statistical analysis using ANOVA and chi-square showed statistically significant difference when the values from experimental animals were compared with those from the control, indicating that the ethanolic extract of Eugenia Jamblana seed possesses hepatotoxic effect. Conclusion: The ethanolic extract of Eugenia jambolana seed extract is toxic to liver as evident by derangement in liver enzyme levels and disturbed liver histology. Keywords: Eugenia Jambolana, Statins, Hepatotoxicity